Forensic Medical Evaluation of a Girl Child Severely Injured in a Pitbull Dog Attack: A Case Report - Aslan, Fatmagül; Timur, Serdar; Teke, Hacer Yaşar; Kurt, Zeynep Aylin (The Bulletin of Legal Medicine, 2022)
In the field of forensic medicine; injuries due to biting can be encountered in a wide range from mild to severe - even causing death. Animal bites are common nowadays and especially affect children. Although not common, such injuries draw attention with the findings of negligence and abuse, and even deliberate injury. In this study, a pediatric case who was bitten by a pittbull dog from various parts of his body, thrown by shaking and treated in intensive care is presented. It was aimed to discuss the forensic medical responsibilities of the Forensic Medicine Units in this and similar negligent injuries, especially by evaluating the case whose opinion was requested in terms of negligence, abuse and deliberate injury due to an incision in the throat.
Keywords: Dog bite; Child; Neglect